New Publication Cultures in the Humanities : Exploring the Paradigm Shift - Dávidházi, Peter (Book collections on Project MUSE., 2019)
The changes we have seen in recent years in the scholarly publishing world - including the growth of digital publishing and changes to the role and strategies of publishers and libraries alike - represent the most dramatic paradigm shift in scholarly communications in centuries. This volume brings together leading scholars from across the humanities to explore that transformation and consider the challenges and opportunities it brings.